Pseudoembryo associated with pseudogestational sac: A novel sonographic finding in ectopic pregnancy. (2019) - Puttagunta, Srikanth; Lee, Stefanie Yan
Abstract: In this case report, we present a case of a hitherto undescribed "pseudoembryo" appearance in a fluid-filled endometrial cavity in ectopic pregnancy. Knowledge of this sonographic finding is clinically important, since the presence of a "pseudoembryo" could lead to the misidentification of a pseudogestational sac as an intrauterine pregnancy in the setting of ectopic pregnancy. This paper discuss reviews the pseudogestational sac and imaging findings which differentiate it from a true intrauterine gestation.